Research on the Expansion Characteristics and Compressive Strength of Mortars Containing Circulating Fluidized Bed Combustion Desulfurization Slag - Zhi Cheng; Zhijun Cheng; Hua Hou; Tao Han; Lan Liu (Advances in Materials Science and Engineering)
Circulating fluidized bed combustion (CFBC) desulfurization slag is a waste residue discharged from coal power plants. In this article, expansion characteristics and compressive strength of mortars containing CFBC desulfurization slag were evaluated, subjected to mechanical grinding time, the amount of additive, and chemical activation. Correlations between the linear expansion rate and compressive strength were investigated. The hydration products of cement-slag cementitious system were analyzed by X-ray diffraction (XRD) and scanning electron microscopy (SEM). The results show that mechanical grinding can increase both the expansion and compressive strength of mortars containing CFBC desulfurization slag, and the compressive strength and linear expansion can develop in coordination. While increasing the amount of the fine desulfurization slag, the linear expansion rate increases, and the compressive strength reaches to the maximum when the amount is 30%. Moderate sodium sulfate as an activator can both promote the compressive strength and increase the expansion of mortars.